2019
DOI: 10.35940/ijitee.a4936.119119
|View full text |Cite
|
Sign up to set email alerts
|

Credit Risk Assessment using Machine Learning Techniques

Abstract: Analysis of credit scoring is an effective credit risk assessment technique, which is one of the major research fields in the banking sector. Machine learning has a variety of applications in the banking sector and it has been widely used for data analysis. Modern techniques such as machine learning have provided a self-regulating process to analyze the data using classification techniques. The classification method is a supervised learning process in which the computer learns from the input data provided and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the following, the most important and commonly used ones for classification problems are presented [11]: Many actual studies use all these evaluation metrics and others to choose the best one. Authors of [27] choose accuracy to conclude that random forest delivered the best results compared to other algorithms. [4] a metric according to profit for peer-to-peer lending as accuracy can be non-sufficient.…”
Section: B Related Work: Algorithms and Metricsmentioning
confidence: 99%
“…In the following, the most important and commonly used ones for classification problems are presented [11]: Many actual studies use all these evaluation metrics and others to choose the best one. Authors of [27] choose accuracy to conclude that random forest delivered the best results compared to other algorithms. [4] a metric according to profit for peer-to-peer lending as accuracy can be non-sufficient.…”
Section: B Related Work: Algorithms and Metricsmentioning
confidence: 99%
“…For credit risk assessment and prediction, Aithal & Jathanna ( 2019 ) compared algorithms such as Support Vector Network, Neural Network, Logistic Regression, Naive Bayes, Random Forest, and Classification and Regression Trees (CART). They found that the most suitable algorithm is Random Forest algorithm, which can predict credit risk of banks with the highest accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The third research, named Credit Risk Assessment using Machine Learning Techniques, focused on the accuracy of credit evaluation by utilizing different machine learning algorithms. Aithal, V and Jathanna, R. D [4] aimed to discover the best analysis model in order to determine credibility. The methodologies, which they selected, are Logistic Regression, Random Forest, Neural Network, Support Vector Network, Naïve Bayes Classifier, and Classification and Regression Trees.…”
Section: Literature Reviewmentioning
confidence: 99%